Rancang Bangun Miniatur Prototype Aircraft Towing Tractor (ATT) Berbasis Arduino Menggunakan Sensor Garis : - Rahmat Putra Adi Wijayanto; Joko Subur; Sinung Widiyanto (J-Eltrik, 2025)
An airport is a complex consisting of the landside and the airside. The airside is a crucial part of airport operations because it encompasses ground handling activities. Ground handling activities are primarily carried out on the apron. Aircraft towing tractors (ATTs), in particular, are vital equipment for aircraft operations in the hangar and on the apron. ATTs are used to tow or push aircraft while on the ground. The majority of these vehicles are still operated by humans. Furthermore, those operating ATTs must have a special permit. In reality, very few people have the permit to operate ATTs, leading to working hours exceeding the standard 8-hour workday. Based on the description, the problem in this research is how to reduce the workload of ATT operators due to the limited number of licensed operators so that it can reduce the occurrence of work accidents due to fatigue in operators. In addition, this research aims to reduce the workload of ATT operators due to the limited number of licensed operators by creating an Arduino-based ATT prototype that can run automatically according to a predetermined path. This tool will function as one of the devices that work in the apron area which is used to push the aircraft from the apron to the taxiway when taking off. The results of the study obtained the maximum load that can be pushed by this tool is 3 Kg. Meanwhile, for testing line sensors and others, it produces very good accuracy, reaching 100%.